Federalismo, integralidade e autonomia no SUS: Desvinculaç\~ao da aplicaç\~ao de recursos federais e os desafios da coordenaç\~ao - Luciana de Barros Jaccoud; Fabiola Sulpino Vieira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– Based on the principles of universality and equality and the guideline of integrality, the Brazilian Public Healthcare System, called Unified Health System (SUS), was constituted as a regionalized and hierarchical services network. There is the recognizing of interdependence between municipalities and between levels of government to guarantee the provision of services. The Union and the states share with the municipalities the responsibility for guaranteeing the constitutional right of access to health goods and services in the country, increasing the requirement for actions cooperation and coordination between the three levels of government. To respond to these questions, intergovernmental relations have undergone progressive transformations since the creation of the system. Recently, in a context of reducing federal social spending, the demand for lesser Union regulation has increased, with changes in federal funds allocation. In the light of the institutional trajectory of the last three decades, as well as the literature on decentralization in health and federalism and social policies, the text has the aim of analyzing the change occurred in 2017 in the form of federal transfers in the SUS. Considering these contributions, the study stresses that the results of decentralization may be negative for efficiency in management and for equity in access to health services. It also emphasizes the relevance of coordination arrangements and mechanisms to improve the health policy outcome and effectiveness in system management. Analyzing the worsening of the financing of the SUS, with a probable reduction of the participation of the Union in the allocation of health resources due to the freezing of its minimum application by EC 95, the study points to the risk of transferring greater responsibilities to states and municipalities, already undermined by underfunding in the health area. Consequently, this changing can cause a reduction in the coordination capacity of the system, a loss of effectiveness, an increase in competition and fragmentation, and an increase in the inequality of access to health goods and services in the country.
Keywords: H51; H77; I18; 330; health expenditure; public health; decentralization; federalism; intergovernmental relations; healthcare financing